Dynamic stall control via adaptive blowing. (November 2016) - Müller-Vahl, Hanns Friedrich; Nayeri, Christian Navid; Paschereit, Christian Oliver; Greenblatt, David
Abstract: An aerodynamic load control concept termed "adaptive blowing" was successfully tested on a NACA 0018 airfoil model at Reynolds numbers ranging from 1.5·10 5 to 5·10 5 . The global objective was to eliminate lift oscillations typically encountered on wind turbine blade sections. Depending on the jet momentum flux, steady blowing from a control slot in the leading-edge region can be utilized to either enhance or reduce lift by suppressing or inducing boundary layer separation respectively. Furthermore, high momentum blowing effectively eliminated the dynamic stall vortex during deep dynamic stall conditions. Based on these previous findings, the present work explores the feasibility of controlling unsteady aerodynamic loads by dynamically varying the jet momentum flux to compensate for transient changes of the inflow. Various scenarios including high amplitude pitching, rapid freestream oscillations and combinations of both were investigated in a custom-built unsteady wind tunnel facility. An iterative control algorithm was implemented which successfully identified the momentum coefficient time profiles required to minimize the lift excursions. The combination of fully suppressing dynamic stall and dynamically adjusting the lift coefficient provided an unprecedented control authority, producing virtually constant phase averaged lift in all cases. Highlights: A novel technique for the control of unsteady aerodynamic loads was experimentally studied in an unsteady wind tunnel facility. The airfoil model is exposed to synchronous, rapid oscillations in angle of attack and relative flow speed. Slot blowing near the leading-edge eliminates the dynamic stall vortex. Virtually constant phase averaged lift is obtained by varying the control jet momentum flux.